1981
DOI: 10.1111/j.1365-2125.1981.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and bioavailability of oral erythromycin.

Abstract: 1 Extent and rate of absorption of erythromycin were studied in 24 healthy volunteers whose disposition kinetics after i.v. injections had been previously documented. 2 Two clinically attractive oral dosage regimens were administered: erythromycin stearate tablets 1 h before meals (Regimen A), and erythromycin base capsules 30 min after start of meals (Regimen B), each equivalent to erythromycin 250 mg, 6 h apart for 9 doses. 3 Serum concentrations of erythromycin measured during the 1st and 9th (steady-state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Large variability among subjects after oral absorption of erythromycin base preparations has been reported by several investigators (17,20,27). This study has also demonstrated substantial variability of the disposition of erythromycin esters (3,36,37).…”
Section: Methodssupporting
confidence: 48%
See 1 more Smart Citation
“…Large variability among subjects after oral absorption of erythromycin base preparations has been reported by several investigators (17,20,27). This study has also demonstrated substantial variability of the disposition of erythromycin esters (3,36,37).…”
Section: Methodssupporting
confidence: 48%
“…The half-life of erythromycin base when administered as enteric-coating base has been reported between 1 and 2 h (7,22,27), but when erythromycin esters were administered as in this study, the half-life of erythromycin base varied between 1.54 and 5.83 h. In most cases, the apparent half-life of erythromycin base was close to that of erythromycin esters, suggesting that the elimination of erythromycin esters and hence the formation of erythromycin base were rate limiting (30).…”
Section: Methodsmentioning
confidence: 99%
“…Although a full dose-ranging study has not been performed with either GF120918A or ketoconazole in this monkey model, these results showing a similar order of magnitude effect with both a selective Pgp/BCRP inhibitor and a dual Pgp/CYP3A inhibitor suggest that in the monkey, Pgp/BCRP, rather than CYP3A, may be the primary factor limiting the absorption of erythromycin. Interestingly, erythromycin demonstrates substantially lower oral bioavailability in the monkey (ϳ2%; Girard et al, 1987;GlaxoSmithKline, unpublished data) than in humans (ϳ30 -65%; Mather et al, 1981). Although beyond the scope of this work, it would be intriguing to compare the in vitro permeability and transporter profile of erythromycin side by side in both human and nonhuman primate intestinal tissue, to ascertain whether differences in transporter activity may contribute to the observed species differences in pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were prompted by numerous reports associating cramping, nausea, vomiting and diarrhoea with erythromycin treatment, which in some cases were severe enough to discontinue treatment (Shoemaker & Yow, 1954;Mather et al, 1981;Downey & Chaput de Saintonge, 1986;Hovi et al, 1987;Shanks et al, 1989). Erythromycin was found to have a disruptive effect on gastrointestinal motor patterns (Pilot et al, 1984;Itoh et al, 1984), even when administered at very low, subtherapeutic doses (Tomomasa et al, 1986;Otterson & Sarna, 1990).…”
Section: Introductionmentioning
confidence: 99%